2016
DOI: 10.1111/odi.12601
|View full text |Cite
|
Sign up to set email alerts
|

Elevated leukocyte count is associated with periodontitis in Korean adults: the 2012–2014 KNHANES

Abstract: An elevated leukocyte count was positively associated with the presence of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…With reference to periodontitis, group 3 (CP only) also had a statistically significant difference when compared with group 4 comprising of healthy subjects. These reiterate the results of Kwon et al., who associated an elevated WBC count positively with periodontitis. Chronic periodontitis patients exhibit a significantly high WBC count, which is also a surrogate marker of the inflammatory response and a potential marker of plaque instability.…”
Section: Discussionsupporting
confidence: 86%
“…With reference to periodontitis, group 3 (CP only) also had a statistically significant difference when compared with group 4 comprising of healthy subjects. These reiterate the results of Kwon et al., who associated an elevated WBC count positively with periodontitis. Chronic periodontitis patients exhibit a significantly high WBC count, which is also a surrogate marker of the inflammatory response and a potential marker of plaque instability.…”
Section: Discussionsupporting
confidence: 86%
“…This study further confirms that periodontitis is associated with leukocytosis, especially with increased numbers of neutrophils. This is in agreement with several studies, convincingly showing that elevations in neutrophils and often lymphocytes are a typical response to periodontitis . This is part of an inflammatory cascade, initiated by the accumulation of periodontopathogenic bacteria subgingivally and continued by a local inflammatory reaction and subsequently by an overall higher systemic inflammation, linked with vascular dysfunction and higher risk of cardiovascular events …”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with several studies, convincingly showing that elevations in neutrophils and often lymphocytes are a typical response to periodontitis. 8,18,24,25 This is part of an inflammatory cascade, initiated by the accumulation of periodontopathogenic bacteria subgingivally and continued by a local inflammatory reaction and subsequently by an overall higher systemic inflammation, linked with vascular dysfunction 26,27 and higher risk of cardiovascular events. 28,29 The main strengths of the present study are a larger sample size compared with previous studies, analysis of association with disease severity measured as PD ≥5 mm and sub-analysis in AgP and CP.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence supports the idea that low-grade inflammation is closely related to the initiation and progression of periodontitis and osteoarthritis. Kwon et al reported that leukocyte count, a nonspecific marker of systemic inflammation, was elevated in the presence of periodontitis in 9,391 Korean adults (27). Levels of proinflammatory cytokines such as IL-6 and TNF are elevated in the synovial fluid and cartilage of patients with osteoarthritis (6), while chronic cytokine elevation is associated with an increased risk of osteoarthritis, according to a prospective study (11).…”
Section: Discussionmentioning
confidence: 99%